ADAPTASI MATERI BUKU PELAJARAN BAHASA BALI KELAS XII SMA/SMK - Ambarwati, Kadek (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2024)
This study examines the adaptation of teaching materials in the Balinese language book for grade XII, especially related to learning Anggah-Ungguhing Basa Bali. The dialogue texts in the book initially displayed conversations that only used Balinese kepara (general) between friends, without displaying the language levels that are important in learning anggah-ungguhing. Therefore, material adaptation was carried out by replacing the dialogue text and adding dialogues that contain various levels of Balinese, both alus language and kepara language. This adaptation aims to improve students' language skills by presenting texts that are more complex than their current level of knowledge. This research method uses a descriptive qualitative approach with content analysis. The results of the adaptation show that students can understand the differences in language levels through role-playing and watching learning videos related to anggah-ungguhing Basa Bali, so that learning becomes more effective and interactive. Evaluation is carried out to measure the effectiveness of the adaptation through practice questions and observation of student participation in class.